Preparation of Chitosan-Polyethylene Oxide-Colocasia esculenta Flour Nanofibers using Electrospinning Method - Riesca Ayu Kusuma Wardhani; Lia Asri; Muhamad Nasir; Bambang Sunendar Purwasasmita (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
Nanofibers have been prepared from the mixture of chitosan, polyethylene oxide (PEO) and Colocasia esculenta flour (CE flour) by using the electrospinning method. Two different nanofibers were formulated, containing chitosan-PEO and chitosan-PEO-CE flour. The higher concentration of PEO (3%chitosan-6%PEO) (w/v) resulted in more uniform chitosan-PEO electrospun nanofibers without beads. Chitosan-PEO-CE flour was prepared by addition of colloidal CE flour into the solution containing 3%chitosan-6%PEO with variation of the CE flour concentration of 5, 15 and 25% (w/v). Scanning Electron Microscopy demonstrated that the average diameter of chitosan-PEO nanofibers was 128±41 nm, whereas the diameter of chitosan-PEO-CE flour nanofibers was 159±45 nm. The diameters of nanofibers increased with the increase of CE flour content. Fourier transform infrared spectra demonstrate the presence characteristic peaks of chitosan, PEO and CE flour.